2020
DOI: 10.3904/kjim.2018.040
|View full text |Cite
|
Sign up to set email alerts
|

Potential etiology, prevalence of cirrhosis, and mode of detection among patients with non-B non-C hepatocellular carcinoma in Korea

Abstract: Background/Aims: We systematically evaluated the clinical characteristics, prevalence of cirrhosis, and mode of detection in virus-unrelated (non-B non-C, NBNC) hepatocellular carcinoma (HCC) patients in Korea. Methods: A total of 447 consecutive treatment-naïve NBNC-HCC adult patients who were registered at the Samsung Medical Center HCC registry in Korea from 2010 to 2013 were analyzed. NBNC was defined as negative hepatitis B surface antigen and negative anti-hepatitis C virus antibody. Presence of cirrhosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
10
3
Order By: Relevance
“…13 But, other studies found that alcohol use and any other identifiable cause were not found in up to 38.0% of the NBNC HCC patients. 14 In this study, it is found that the proportion of HBcAbpositive was up to 80% in all NBNC HCC cases. The fatty liver and alcohol liver were less than 20% in the NBNC HCC cases and the proportion of cirrhosis was less than 40%.…”
Section: Discussionmentioning
confidence: 56%
“…13 But, other studies found that alcohol use and any other identifiable cause were not found in up to 38.0% of the NBNC HCC patients. 14 In this study, it is found that the proportion of HBcAbpositive was up to 80% in all NBNC HCC cases. The fatty liver and alcohol liver were less than 20% in the NBNC HCC cases and the proportion of cirrhosis was less than 40%.…”
Section: Discussionmentioning
confidence: 56%
“…HBV infection is the main cause of HCC [1,2]. But the mechanisms of carcinogenesis are different compared with NBNC-HCC [20,22]. HBV is a DNA virus that causes malignant transformation of hepatocytes mainly through gene integration into chromosomes and activation of oncogenes [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…However, both of them are caused by chronic viral infection. The etiology of NBNC-HCC is mostly a metabolic factor [20,21]. The tumor physiological characteristics are quite different from HCC caused by HBV and HCV.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the United States, the incidence of HCC has increased 3‐fold since the mid‐1970s 12 in conjunction with the increasing prevalence of diabetes 13 and obesity 14 . Therefore, the contribution of metabolic disorders to the risk of HCC is more important than in the past 15 …”
Section: Introductionmentioning
confidence: 99%
“…14 Therefore, the contribution of metabolic disorders to the risk of HCC is more important than in the past. 15 Numerous previous studies have shown an association between general obesity and HCC. [16][17][18][19][20] To date, body mass index (BMI) has been used as an anthropometric measurement for adiposity in most studies.…”
mentioning
confidence: 99%